Results of Positive Solutions for the Fractional Differential System on an Infinite Interval. (5th May 2020) - Wang, Ying; Yang, Jun; Zi, Yumei
Abstract : The chief topic of this paper is to investigate the fractional differential system on an infinite interval. By introducing an appropriate compactness criterion in a special function space and applying the Schauder fixed-point theorem and the Banach contraction mapping principle, we established the results for the existence and uniqueness of positive solutions. An example is then given to show the utilization of the main results.